PENANGANAN KONDISI TRAUMATIK ANAK KORBAN KEKERASAN SEKSUAL MENGGUNAKAN ART THERAPY: SEBUAH KAJIAN LITERATUR [HANDLING OF TRAUMATIC CONDITIONS OF CHILD VICTIMS OF SEXUAL VIOLENCE USING ART THERAPY: A LITERATURE REVIEW] - Vera Maulida Rahmah; Ismilia Muwaffaqoh Arifah; Citra Widyastuti (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2021)
Cases of sexual violence in Indonesia are increasing, and among the victims are children who do not understand sexuality. Sexual violence against children is considered a crime that can cause long-lasting negative and traumatic effects, while children do not understand that they are victims, and even children find it difficult to reveal what happened. Art therapy as a therapy using art, is considered to be an alternative to express feelings that are difficult to express and describe real conditions. Thus, this study aims to determine the implementation of art therapy in overcoming traumatic conditions in child victims of sexual violence. In this study, the author uses a type of library research method, by reviewing some literature from books and scientific journals. The results that the authors found by examining theories indicate that art therapy can be one of the therapies that can deal with traumatic problems of children who are victims of sexual violence. With art therapy, children can express their feelings and describe the conditions that occur through art media which are interpreted through pictures and colors.